1997
DOI: 10.1002/j.1467-8438.1997.tb00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Reclaiming the Mother‐daughter Relationship after Sexual Abuse

Abstract: This paper seeks to provide direction to therapists working with mothers and daughters after a disclosure of father‐daughter sexual abuse. The importance of the mother's belief in and support for the child's recovery is highlighted, as are some of the cultural assumptions about mothers and daughters which negatively impact on the relationship. Despite paying lip service to offender responsibility, there continues to be a culture of mother blaming in the child sexual abuse and family therapy literature on inces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 22 publications
0
23
0
2
Order By: Relevance
“…Em intervenções em situação de crise, pode ser necessário ampliar as sessões oferecidas à criança e/ou a sua família, pelo menos no estágio inicial do processo terapêutico (Miller & Dwyer, 1997), tendo em vista as repercussões que a revelação do abuso pode acarretar em todo o sistema familiar. Com sessões mais frequentes e com o estabelecimento de uma relação de confiança entre todos, criança, famí-lia e terapeuta, as mudanças e os ajustes na rotina da família são trabalhados de forma mais contínua, fazendo com que aos poucos cada membro da família possa expressar e elaborar sua dor.…”
Section: Atendimento a Mães E Abusadoresunclassified
“…Em intervenções em situação de crise, pode ser necessário ampliar as sessões oferecidas à criança e/ou a sua família, pelo menos no estágio inicial do processo terapêutico (Miller & Dwyer, 1997), tendo em vista as repercussões que a revelação do abuso pode acarretar em todo o sistema familiar. Com sessões mais frequentes e com o estabelecimento de uma relação de confiança entre todos, criança, famí-lia e terapeuta, as mudanças e os ajustes na rotina da família são trabalhados de forma mais contínua, fazendo com que aos poucos cada membro da família possa expressar e elaborar sua dor.…”
Section: Atendimento a Mães E Abusadoresunclassified
“…Opplevelsen av hendelsen kan påvirkes av en rekke forhold som overgripers kjønn, naerhet til overgriper, grad av tvang og den utsattes og overgripers alder (Miller et al, 1997;Smith et al, 2000;Mannon og Leitschuh, 2002, s. 150). Spørsmålene i vår undersø-kelse som skal fange opp overgrepserfaringer ivaretar hver av disse dimensjonene, uavhengig av hverandre.…”
Section: Kartlegging Av Seksuelle Krenkelserunclassified
“…The good mother myth demands that the mother will always know what is best and how to respond in a selfless and assured way. Good mother myths distort the realities of child sexual abuse and its impact on the mother-child relationship, thereby scapegoating the mother as a failure, as a bad mother (Miller & Dwyer, 1997).…”
Section: Mother-blaming and Child Sexual Abusementioning
confidence: 99%
“…Miller and Dwyer (1997) reported that there are not any competent studies that have determined that mothers usually knew of the abuse prior to disclosure or that they were collusive. Contradictory to previous perceptions, it has been found that when mothers did learn of the sexual abuse, they tended to notify someone outside the family (Risely-Curtiss & Heffeman, 2003).…”
Section: Mother-blaming and Child Sexual Abusementioning
confidence: 99%
See 1 more Smart Citation